Ke Arah Pendidikan Bermutu - Saleh, Ahmad (Penerbit Universiti Sains Malaysia, 1980)
The Editorial Board would like to record here its thanks to the writer of this article for permission to print the article in this journal. This article, with slight modification and the addition of synopsis in English by the Editorial Board, is the speech entitled "Ke Arah Pendidikan Bermutu" delivered by the writer as the Director of Educational Planning and Research,Ministry of Education, Malaysia to the Association of Organisers of the Schools, Peninsular Malaysia, on 29th September, 1979. The Editorial Board believes that the article provides the readers with valuable information on the current concern of the Ministry of Education.